2019
DOI: 10.1007/s11250-019-01989-w
|View full text |Cite|
|
Sign up to set email alerts
|

In vivo digestibility of six selected fodder species by goats in northern Ghana

Abstract: An in vivo digestibility trial was conducted to evaluate the digestibility of six forages. These were selected indigenous browse species and groundnut haulms in Lawra and Jirapa Districts of the Upper West Region of Ghana. Groundnut haulms served as a control due to its known good digestibility in small ruminants. Thirty West African Dwarf (WAD) young castrated billy goats with a mean age of 8 months were used. The average live body weight was 8.9 ± 0.1 kg. The animals were randomly assigned to the six treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…However, Trujillo et al (2010) demonstrated that the Daisy II method underestimated DM and neutral detergent fiber disappearance values, compared to in situ methods. The IVDMD values of the present study were higher than that reported by Avornyo et al (2019) in Ghana, and similar to those reported for Olafadehan and Okunade (2018) in Nigeria. Both studies evaluated the nutritional value of trees and shrubs consumed by goats.…”
Section: In Vitro Dry Matter Digestibilitysupporting
confidence: 86%
“…However, Trujillo et al (2010) demonstrated that the Daisy II method underestimated DM and neutral detergent fiber disappearance values, compared to in situ methods. The IVDMD values of the present study were higher than that reported by Avornyo et al (2019) in Ghana, and similar to those reported for Olafadehan and Okunade (2018) in Nigeria. Both studies evaluated the nutritional value of trees and shrubs consumed by goats.…”
Section: In Vitro Dry Matter Digestibilitysupporting
confidence: 86%
“…The study was carried out for 70 days, consisting of a 28-day adaptation period, a 42-day collection period, including 14 days of feeds, feces, and urine collection, and measuring body weight gain. In vivo digestibility tests were carried out using the total collection method, according to Avornyo et al [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…They showed that these peruse plants act as an elective feed source particularly during the long dry period in the semi-parched zone due to their high potential protein digestibility. In a study conducted by Avornyo et al [ 90 ], six fodder species ( Annona senegalensis, Ficus gnaphalocarpa, Pericopsis laxiflora, Pterocarpuserinaceus, Afzelia africana, and Arachis hypogaea ) were fed to dwarf goats in West Africa. The study found that the digestibility indices of four of the feeds had DM contents of 60 to 75%, and the digestibility indices of browse species, like groundnut haulm, were within the usual range for recommended fodder species.…”
Section: Alternative Feed Resources In Small Ruminant’s Nutritionmentioning
confidence: 99%
“… * DM: dry matter, OM: organic matter, CP: crude protein, EE: ether extract, NDF: neutral detergent fiber, ADF:acid detergent fiber. Adapted from: 1 Adelusi et al [ 93 ], 2 Haruna et al [ 89 ], 3 Avornyo et al [ 90 ], 4 Ajagbe et al [ 94 ], 5 Yang et al [ 76 ], 6 Ahmed et al [ 95 ], 7 Wadhwa et al [ 70 ], 8 Khaing et al [ 85 ], 9 Sahoo et al [ 51 ], 10 Nkosi et al [ 83 ], 11 Gebremariam and Brhanu [ 67 ], 12 Hao et al [ 97 ], 13 Mengistu et al [ 98 ]. …”
Section: Alternative Feed Resources In Small Ruminant’s Nutritionmentioning
confidence: 99%